(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the relevance of preserving national identity in the context of globalization, as well as the positive and negative aspects of globalization. In particular, it examines the impact of globalization processes on economic, political, and cultural life, and highlights the importance of preserving national values, language, customs, and traditions. The article also explores the role of national identity in social development based on Samuel Huntington’s views on cultural differences and identity issues presented in The Clash of Civilizations.